Synthesis, characterization of polytridecamethylene 2,6-naphthalamide as semiaromatic polyamide containing naphthalene-ring (eXPRESS Polymer Letters)
A novel engineering plastic polytridecamethylene 2,6-naphthalamide (PA13N) was prepared via a reaction of 2,6-naphthalene dicarboxylic acid and 1,13-tridecanediamine through a three-step procedure. The structure of synthesized PA13N was characterized by elemental analysis, Fourier transform infrared (FT-IR) spectroscopy and proton nuclear magnetic resonance (1H-NMR). The thermal behaviors were determined by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA). The solubility, water-absorbing capacity, and mechanical properties of PA13N have also been investigated. Melting temperature (Tm), glass transition temperature (Tg) and decomposition temperature (Td) of PA13N are 288, 129 and 492°C, respectively. The results show that the heat resistance and mechanical properties of PA13N are near to those of polynonamethylene terephthalamide (PA9T), and PA13N is a promising heat-resistant and processable engineering plastic.